Exploring Factors Affecting the Adoption of Flexible Learning Modality by Public University Students in Masbate, Philippines - Erdee Cajurao; Michael Ogaya; Cesar Almonicar, Jr; Grace Abella; Joper Escalante (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study explored factors influencing the adoption of flexible learning by university students at Dr. Emilio B. Espinosa Sr. Memorial State College of Agriculture and Technology (DEBESMSCAT), a public university in Masbate, Philippines. A descriptive research survey approach was used with 1,137 respondents. Students relied on parents or guardians (45.3%) for support and used smartphones (57.4%) and basic cellphones/keypads (24.4%) for flexible learning. Most had internet access (75.5%) but relied on mobile data (72.8%), the slowest type of connection. Online (23.5%) and modular (22.9%) instruction was preferred over on-campus classes. Key barriers were lack of budget for load allowance (32.9%), unstable internet connection (31.4%), and unavailability of gadgets (15.2%). The study recommends addressing financial barriers for better academic outcomes.